2018
DOI: 10.1080/09737766.2017.1332610
|View full text |Cite
|
Sign up to set email alerts
|

Highly Cited Researchers 2014 and 2015: An investigation of some of the world's most influential scientific minds on the institutional and country level

Abstract: For several years, Clarivate Analytics, formerly the IP & Science business of Thomson Reuters, has published a list of researchers who have published the largest number of highly cited papers in a particular discipline (see www.highlycited.com). These researchers are described by Clarivate Analytics as highly-cited researchers (HCRs) or as some of the world's most influential scientific minds. Whereas the HCR 2014 list refers to the publication years 2002 to 2012, the HCR 2015 list which was published a few mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…10 A U.S. Department of Energy advisory committee recently announced that Chinese researchers produce most of the world's top research in energy storage and sustainable energy science. 11 A 2020 study by Clarivate found that approximately 12 percent of the most widely cited researchers globally resided in China, up from about 5 percent in 2014 and just 1 percent in 2001 12.…”
mentioning
confidence: 99%
“…10 A U.S. Department of Energy advisory committee recently announced that Chinese researchers produce most of the world's top research in energy storage and sustainable energy science. 11 A 2020 study by Clarivate found that approximately 12 percent of the most widely cited researchers globally resided in China, up from about 5 percent in 2014 and just 1 percent in 2001 12.…”
mentioning
confidence: 99%